Development strategies for the satellite flight software on-board Meteosat Third Generation. (April 2018) - Tipaldi, Massimo; Legendre, Cedric; Koopmann, Olliver; Ferraguto, Massimo; Wenker, Ralf; D'Angelo, Gianni
Abstract: Nowadays, satellites are becoming increasingly software dependent. Satellite Flight Software (FSW), that is to say, the application software running on the satellite main On-Board Computer (OBC), plays a relevant role in implementing complex space mission requirements. In this paper, we examine relevant technical approaches and programmatic strategies adopted for the development of the Meteosat Third Generation Satellite (MTG) FSW. To begin with, we present its layered model-based architecture, and the means for ensuring a robust and reliable interaction among the FSW components. Then, we focus on the selection of an effective software development life cycle model. In particular, by combining plan-driven and agile approaches, we can fulfill the need of having preliminary SW versions. They can be used for the elicitation of complex system-level requirements as well as for the initial satellite integration and testing activities. Another important aspect can be identified in the testing activities. Indeed, very demanding quality requirements have to be fulfilled in satellite SW applications. This manuscript proposes a test automation framework, which uses an XML-based test procedure language independent of the underlying test environment. Finally, a short overview of the MTG FSW sizing and timing budgets concludes the paper. Highlights: Layered model-based architecture for satellite Flight Software (FSW). FSW development life cycle model by mixing plan-driven and agile approaches. FSW testing automation tools. Implementation of the proposed strategies in a real satellite project. Measurement of the FSW sizing and timing budgets.